"Welfare Queens" and "Teen Moms": How the Social Construction of Fertile Women Impacts Unintended Pregnancy Prevention Policy in the United States. (August 2013) - James, E. Angel; Rashid, Moira
In the United States, unintended pregnancy is a serious health, social, and economic concern. However, the existing prevention policies have proven ineffective at decreasing the rate of unintended pregnancy at a national level. This lack of effective national prevention policy is better understood when viewed through the lens of a policy theory that incorporates an understanding of social construction and its effects on policy development. Through the application of one such policy theory, this article explores how the social construction of fertile women in the United States affects previous and recently enacted unintended pregnancy prevention policies.